2022
DOI: 10.1093/dote/doac037
|View full text |Cite
|
Sign up to set email alerts
|

Robotic versus thoraco-laparoscopic minimally invasive Ivor Lewis esophagectomy, a matched-pair single-center cohort analysis

Abstract: Minimally invasive esophagectomy (MIE) is becoming more widespread with a documented improvement in postoperative morbidity based on level I evidence. However, there is a lack of consensus regarding the optimal MIE approach, conventional thoracoscopy/laparoscopy vs robotics as well as the ideal anastomotic technique. All patients who underwent MIE via an Ivor Lewis approach with a side-to-side stapled anastomosis were included. The thoracoscopy-laparoscopy (TL) group was compared to the robotic group with resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In their experience, rates of anastomotic leakage have been favorable, ranging from 2% to 8% 22–24 . However, at this time, there are no prospective randomized trials comparing different ILE approaches (Open, CA and RA), and, including the current study, only five single‐center retrospective comparative studies have been reported 25–28 . Weindelmayer et al, 28 comparing the RA group of 47 cases with the Open group of 159 cases, reported a significantly longer operative time in the RA group, but similar rates of anastomotic leakage (RA 2.1% vs. Open 6.9%, p = .56) and a 90‐day mortality (RA 2.1% vs. Open 1.9%, p = .65).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In their experience, rates of anastomotic leakage have been favorable, ranging from 2% to 8% 22–24 . However, at this time, there are no prospective randomized trials comparing different ILE approaches (Open, CA and RA), and, including the current study, only five single‐center retrospective comparative studies have been reported 25–28 . Weindelmayer et al, 28 comparing the RA group of 47 cases with the Open group of 159 cases, reported a significantly longer operative time in the RA group, but similar rates of anastomotic leakage (RA 2.1% vs. Open 6.9%, p = .56) and a 90‐day mortality (RA 2.1% vs. Open 1.9%, p = .65).…”
Section: Discussionmentioning
confidence: 63%
“…[22][23][24] However, at this time, there are no prospective randomized trials comparing different ILE approaches (Open, CA and RA), and, including the current study, only five single-center retrospective comparative studies have been reported. [25][26][27][28] Weindelmayer et al, 28 comparing the RA group of 47 cases with the Open group of 159 cases, reported a significantly longer operative time in the RA group, but similar rates of anastomotic leakage (RA 2.1% vs. Open 6.9%, p = .56) and a 90-day mortality (RA 2.1% vs. Open 1.9%, p = .65). Regarding the comparison between RA and CA, Zhang et al 25 and Tagkalos et al 26 demonstrated no significant difference in leakage rates between the two groups, which was performed with a circular stapled or hand-sewn technique (Zhang et al: RA 7.6% vs. CA 4.5%, p = .727, Tagkalos et al: RA 12.5% vs. CA 12.5%, p = .966).…”
Section: Surgical Outcomesmentioning
confidence: 99%
“…[9] In the following decade, many medical centers have reported the implementation of RAMIE. [5,10] Previous studies have shown that robot-assisted esophagectomy has better short-term outcomes compared with video-assisted thoracoscopic esophagectomy. [11] However, few studies have compared the mid -and long-term prognosis between RAMIE and VAMIE.…”
Section: Discussionmentioning
confidence: 99%
“…On multivariable analysis, conversion rate, margin positivity, and LN harvest remained superior in RAMIE 36 . Single‐center retrospective reviews have found similarly improved perioperative outcomes with a robotic approach 37 …”
Section: Gastrointestinal Surgerymentioning
confidence: 91%
“…36 Single-center retrospective reviews have found similarly improved perioperative outcomes with a robotic approach. 37…”
Section: Robotic Versus Laparoscopic Esophagectomymentioning
confidence: 99%